ORGANISATIONAL AND ECONOMIC MECHANISM FOR PREVENTING CORRUPTION IN PUBLIC AUTHORITIES IN THE CONTEXT OF ENSURING EFFECTIVE REGULATION OF THE HEALTHCARE SYSTEM - POPELO, Olha (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The article is devoted to the research of the impact of the phenomenon of "corruption" in the state authorities on the functioning of the healthcare system in Ukraine. The article considers not only the impact of corruption on the functioning of the healthcare system in general, but also such issues as state regulation of medical institutions, redistribution of management functions in the healthcare system, granting autonomous status to medical institutions (autonomization), and financing of the healthcare system in general. The article describes the Ukrainian legislative anti-corruption regulators, institutional levers of the Cabinet of Ministers of Ukraine, local administrations and executive authorities. The author presents an organizational and economic mechanism for preventing corruption in the healthcare sector. The mechanism is based on the system of institutional and legislative regulators, and also reveals their subordination and sequence of influence. The main elements of the organizational and economic mechanism for preventing corruption in the healthcare sector are anti-corruption legislation, legalization of the healthcare market, decentralization of the healthcare management system, autonomy of healthcare institutions, openness of financial and economic activities, and transparency of information and communication activities. The presented scheme of the mechanism reflects the elements of regulatory prevention of corruption, as well as the subordination and sequence of activation of elements in healthcare management. the proposed mechanism for preventing corruption in healthcare allows for effective and anti-corruption management of healthcare institutions at all levels of subordination to state and local authorities. The author formulates conclusions regarding the possibility of corruption's impact on the functioning of the healthcare sector. The author analyses the possibility of creating and implementing a rational organizational and economic mechanism for preventing corruption in public authorities in the context of ensuring effective regulation of the healthcare system.
Keywords: corruption; efficiency of regulation; state authorities; local authorities; health care system; regulatory levers; organizational and economic mechanism